L’ « erreur sémantique » comme conséquence de l’interprétation globale du texte. La traduction en italien du quasi-monologue Une légère blessure de Laurent Mauvignier - Bramati, Alberto (mediAzioni, 2023)
The meaning of texts that play on the different levels of language depends not only on the meaning of the words, but also on lexical and syntactic choices, figures of speech, melodic-rhythmic effects – in other words, on what we call “style.” Since it is by definition impossible to reproduce all these levels, the translator is always forced to make choices. It is therefore on the basis of their overall interpretation of the text that translators propose solutions to the various problems posed by the source text. In this study, to show the reasons that can lead a translator to make choices that could easily be considered “errors,” we will present a few examples of lexical, grammatical, rhetorical, and melodic-rhythmic problems taken from our translation into Italian of a play by Laurent Mauvignier, Une légère blessure (2016).